PEMBERLAKUAN SANKSI PIDANA TERHADAP PELAKU ABORSI DI INDONESIA: STUDI KOMPARATIF WETBOEK VAN SSTRAFTRECH (WVS) DAN UNDANG-UNDANG NO. 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA (KUHP) - Kusuma, Made Adi (Ilmu Hukum Prima (IHP), 2024)
Abortion is a classic issue that is always interesting to discuss. The polarization of differences in views between the pros and cons of abortion is an extreme defense of the right to life of the fetus or defense of the interests of the pregnant woman. Abortion due to unwanted pregnancy is an issue that has returned to the fore. This research will discuss abortion in a comparative way between Wetboek van Straftrech (WVS) and Law no. 1 of 2023 concerning the Criminal Code (KUHP). The Criminal Code places abortion as a criminal offense. However, abortion is still very necessary for some people for certain reasons. Whether it's for medical reasons, such as the mother's life being threatened and so on.